Gender analysis and reform of irrigation management: concepts, cases, and gaps in knowledge: proceedings of the Workshop on Gender and Water, 15-19 September 1997, Habarana, Sri Lanka - Merrey, Douglas J.; Baviskar, S. (International Water Management Institute, 1998)
Proceedings of the workshop which focused particularly on gender analysis of rights to land and water, the implications of privatization and water markets for women's access to resources, how women (as well as men) can participate fully in collective action projects and the relation between problems like water scarcity and pollution, multiple uses of water in irrigation systems and gender.